2019
DOI: 10.1177/1078155219846952
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant use of capecitabine and proton pump inhibitors – Is it safe?

Abstract: Background Capecitabine is a commonly used oral chemotherapy agent. Recent data suggest that concurrent use of proton pump inhibitors may reduce the efficacy of capecitabine by decreasing its absorption through increased gastric pH. Since proton pump inhibitors are widely used, we evaluated the supportive evidence for the probability of occurrence and potential seriousness of this drug interaction. Methods The probability of occurrence was evaluated based on the clinical, pharmacokinetic and in vitro evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 18 publications
4
25
1
Order By: Relevance
“…Conversely, before our study, negative results regarding the use of PPIs and capecitabine were reported [ 19 , 20 , 21 ]. In a retrospective post hoc analyses of the TRIO-013/LOGiC study, the concomitant use of PPIs with capecitabine and oxaliplatin (CapeOx) with or without lapatinib was evaluated in patients with ERBB2/HER2-positive metastatic gastroesophageal cancer [ 20 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Conversely, before our study, negative results regarding the use of PPIs and capecitabine were reported [ 19 , 20 , 21 ]. In a retrospective post hoc analyses of the TRIO-013/LOGiC study, the concomitant use of PPIs with capecitabine and oxaliplatin (CapeOx) with or without lapatinib was evaluated in patients with ERBB2/HER2-positive metastatic gastroesophageal cancer [ 20 ].…”
Section: Discussionmentioning
confidence: 56%
“…Interesting preclinical and clinical data pointed out the possibility to revert drug resistance of tumor cells by using high dose PPIs [ 4 , 5 , 6 , 7 , 8 , 9 ]. However, there were also recent data which reported negative retrospective results with the concurrent use of PPIs and capecitabine in different setting of patients affected with GI cancer [ 19 , 20 , 21 ]. Our study for the first time investigated in a randomized phase II trial the concurrent use of repurposed high-dose rabeprazole combined with low-dose metronomic capecitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant use of Maalox, an antacid containing magnesium hydroxide and aluminum hydroxide, did not significantly affect the extent and rate of absorption of capecitabine [16]. PPIs induce a stronger acid suppression than antacids, but the dissociation constant of capecitabine is 8.8, indicating that its absorption might be minimally affected in the elevated pH conditions (pH 3.5–4.9) induced by PPIs [7]. Therefore, drug‐drug interaction studies are warranted to understand the effect of PPIs on the pharmacokinetics of capecitabine.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of absorption of orally administered anticancer agents such as capecitabine in the gastrointestinal tract could significantly affect the pharmacokinetic profile of those drugs and thereby their safety and efficacy. The bioavailability of tyrosine kinase inhibitors is reduced with the administration of proton pump inhibitors (PPIs) because the solubility of the drugs is decreased in conditions of elevated intragastric pH [7]. However, whether the acidic environment of the stomach influences the absorption of capecitabine remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] However, pharmacokinetic and in vitro studies have failed to identify the mechanisms of the interaction between PPIs and capecitabine. 19 Furthermore, it is unclear whether the potentially negative effects of PPIs might also involve intravenously administered cytotoxic agents.…”
Section: Introductionmentioning
confidence: 99%